The Effect of Using Context-Based Learning Videos on Fluid Materials on Students Critical Thinking Ability - Yulaisa, Gusni; Desnita, Desnita (Jurnal Pijar Mipa, 2024)
Starting from the learning media used in schools not being able to prepare students to think critically, using context-based learning videos is one solution to improve students' critical thinking abilities. This research aims to see the effect of context-based learning videos on fluid material on the essential thinking abilities of class XI students at SMA Negeri 5 Solok Selatan. This study uses a quasi-experiment with a posttest-only control design. The research population was all class XI IPA students at SMAN 5 Solok Selatan registered in the 2022/2023 academic year. Purposive sampling was chosen as a sampling technique, so classes XI IPA 1 and XI IPA 2 were taken as research samples. The instrument used to obtain critical thinking ability data was a written test using 8-item essay questions. Normality, homogeneity, and t-tests were used in the data analysis. The measurement results show that experimental class students (80,38) have higher critical thinking skills than the control class (70,56). Statistical analysis with the t-test shows that that tcount > ttable (3,41 > 2.006) means the working hypothesis is accepted. So, it can be concluded that using context-based learning videos on fluid material affects students' critical thinking abilities.